Endogenous morphine: up-to-date review 2011 - Stefano, G B; Ptáček, R; Kuželová, H; Kream, R M (Folia biologica, 2012)
Positive evolutionary pressure has apparently preserved the ability to synthesize chemically authentic morphine, albeit in homeopathic concentrations, throughout animal phyla. Despite the establishment of a progressively rigorous and mechanistically focused historical literature extending from the mid 1970s to the mid 1980s that supported the expression of chemically authentic morphine by animal cellular and organ systems, prejudicial scepticism and early dismissal by scientists and clinicians most often obscured widespread acceptance of the biological importance and medical implications of endogenous morphine. The current critical paper presents and evaluates key recent coordinated studies in endogenous morphine research, highlighting those that have advanced our understanding of the functional roles of cognate alkaloid-selective μ(3) and μ(4) opiate receptors. We propose that the expression of endogenous morphine by animal and human cells is designed to mediate homeopathic regulation of metabolic activity via activation of cognate μ(3) and μ(4) receptors that serve as transductive conduits for shortcircuit Ca(++) fluxes. The implications of endogenous morphine coupling to nitric oxide regulation of mitochondrial function, with special reference to the cardiovascular system, are now formulated after many years of neglect.
Keywords: Models, Chemical; kardiovaskulární systém; Animals; dopamin; Dopamine; oxid dusnatý; Nitric Oxide; morfin; Humans; Models, Biological; Receptors, Opioid, mu; mitochondrie; Gene Expression Regulation; biologické modely; Cardiovascular System; chemické modely; regulace genové exprese; zvířata; receptory opiátové mu; lidé; Signal Transduction; Mitochondria; signální transdukce; Morphine